The Effect of Illumination, Electrode Distance, and Illumination Periods on the Performance of Phototrophic Sediment Microbial Fuel Cells (PSMFCs) - Harimawan, Ardiyan; Devianto, Hary; Khodiyat, Nicholas; Gatalie, Kreszen Livianus; Aslan, Christian (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Microbial fuel cells (MFCs) can potentially be used to overcome issues with battery powered light buoys and their frequent maintenance. In this study, a phototrophic sediment microbial fuel cell (PSMFC) was chosen, as the microalgae provide oxygen to be reduced on the cathode and to release the necessary nutrients for the bacteria on the anode. To achieve this, we studied the effect of illumination, the period of the illumination, and the distance between 9-cm2 stainless steel mesh electrodes on the performance of the MFC. The illuminated cells were able to produce higher OCP (max. 205.2 mV) and higher power density (max. 0.68 mW/m2). However, the highest current was achieved during the unilluminated variation (max. 5.3 μA unilluminated and 3.3 μA illuminated). Prolonged illumination produced a higher OCP, current, and power density. A longer electrode distance produced a higher OCP, power density, and current. SEM analysis showed that biofilm formation tended to be scattered at lower electrode distance and more clumped (filling the anode area) at higher electrode distance. Through FTIR analysis, it was found that all MFC variations had the same organic matter, but a more concentrated organic content was found in the MFC at longer electrode distances.